Pengaruh Kepemimpinan dan Profesionalisme Kepala Sekolah Terhadap Motivasi Kinerja Guru : Di Rumpun SD Gugus 02 Depok - Nur Azizah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This reseach by a quantitative approach with descriptive for design correlational regresional. The populations in this study were 71 teachers. On that focused on examination. Research data was collected by using a questionnaire instrument, with referred to the Likert scale. The validity level of the instrument that had been developed was tested by using Pearson Product Moment technique. While the instrument of reliability estimates was tested by using Cronbach alpha formula. The data analysis techniques in this study were included descriptive analysis, test analysis requirements include normality testing Kolmogorov Smirnov techniques and linearity test with linearity, homogeneity and heteroskedastisits test then the hypothesis test that includes a t-test to know the - correlation between variables partially, and multiple regression test to determine the correlation of these variables together. The F-test, determination test, and analysis of the results of this study conducted with SPSS version 21 for Window. The final outcome studies proof that (1). if the principal’s leadership scores (X1) rose by one point or one score, it will be followed by an increase on the motivation of teacher’s performance (Y) by 0.713 points. (2) if the principal’s professionalism (X1) rose one point or – one score, it will be followed by an increase on the motivation of teacher’s performance (Y) by 0.760 points. (3). If b1 = 0.282 states that if X1 increases, then Y will increase by 0.282, by assuming that there is no additional (constant) value of X2. b2 = 0.507 states that if X2 increases, then Y will increase by 0.507, by assuming that there is no additional (constant) value of X1. The magnitude of the relationship between the variables can be seen from the determination, (1) variations on the motivation of teacher’s performance that are influenced by the principal's leadership are 64.7% and 63.4% are influenced by external factors. (2) variable Y is influenced by X2 are 0.696. The meaning of this coefficient is that the relative contribution given by 69.6%, while 31.4% is influenced by other variables (3) the relative contribution provided by a combination of variables X1 and X2 to Y is at 71.9% while the rest is influenced by other variables.